Kinerja Perangkat Desa dalam Pelaksanaan Administrasi Keuangan di Kantor Desa Winongan Lor Kecamatan Winongan Kabupaten Pasuruan - Muhammad Fernanda Samlin Tamawa Putra; Deby Febriyan Eprilianto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The implementation of financial administration in the Winongan Lor Village Office is carried out by the Village Secretary with the Head of Financial Affairs (Kaur Keuangan) along with 1 (one) Kaur Keuangan staff. However, there are still problems with the performance of village officials in implementing village financial administration, namely that village officials do not complete financial reports on time and the results of financial reports reported to the public exceed the specified deadline. Therefore, this study aims to determine and describe the performance of village officials in implementing financial administration in the Winongan Lor Village Office. This study uses descriptive qualitative research. This study focuses on employee performance indicators from Mitchell which include work quality, initiative, punctuality, ability, and communication. The data sources for this study use primary data sources and secondary data sources. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis techniques use narrative analysis techniques. The results of this study indicate that the work quality indicator has produced good work quality, the initiative indicator has been initiated well. The timeliness indicator has not been carried out properly because there are still delays in the budgeting and financial reporting processes. The ability indicator has shown good ability. The communication indicator has been carried out well.